2017
DOI: 10.1001/jamaophthalmol.2017.3782
|View full text |Cite
|
Sign up to set email alerts
|

Automated Grading of Age-Related Macular Degeneration From Color Fundus Images Using Deep Convolutional Neural Networks

Abstract: IMPORTANCE Age-related macular degeneration (AMD) affects millions of people throughout the world. The intermediate stage may go undetected, as it typically is asymptomatic. However, the preferred practice patterns for AMD recommend identifying individuals with this stage of the disease to educate how to monitor for the early detection of the choroidal neovascular stage before substantial vision loss has occurred and to consider dietary supplements that might reduce the risk of the disease progressing from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
335
1
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 522 publications
(363 citation statements)
references
References 34 publications
2
335
1
3
Order By: Relevance
“…Their model was able to do that, with a root mean squared error of 12.9 letters. 52 They trained their programs with different MLCs with over 130 000 colour fundus images from 4613 patients. 50 These results should be considered within the context of the lower intersession reliability of visual acuity measurement in AMD.…”
Section: Assessment Of Age-related Macular Degenerationmentioning
confidence: 99%
“…Their model was able to do that, with a root mean squared error of 12.9 letters. 52 They trained their programs with different MLCs with over 130 000 colour fundus images from 4613 patients. 50 These results should be considered within the context of the lower intersession reliability of visual acuity measurement in AMD.…”
Section: Assessment Of Age-related Macular Degenerationmentioning
confidence: 99%
“…Over the past decade, automated techniques for the assessment of AMD, via feature extraction from small retinal image datasets (<1000), have been reported with variable accuracy. More recent reports provide novel data on the accuracy of deep‐learning systems for the detection of AMD . The majority of these studies have utilized the Age‐Related Eye Disease Study (AREDS) participants to develop and test the accuracy of their DLAs .…”
Section: Discussionmentioning
confidence: 99%
“…Although they used late AMD as a classifier, this included geographic atrophy which our DLA does not classify as referable AMD. A binary classification was used to determine referable AMD (≥intermediate AMD) in the investigations by Ting et al (2017) and Burlina et al (2017) who both reported AUC's between 0.93 and 0.96. Whilst these findings are similar to the current study, they are not directly comparable as only those classified as neovascular AMD we considered referable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a deep-learning algorithm classified age-related macular degeneration and diabetic retinopathy from optical coherence tomography images of the retina 1 . Both of these eye conditions and others (such as glaucoma and macular oedema), have also been automatically assessed by deep learning trained on fundus images [2][3][4] (a retinal fundus image is a photograph of the internal surface at the back of the eye). In all these tests, the algorithms, which had been trained on hundreds of thousands of medically labelled images, performed on par with teams of human ophthalmologists and better than many individual experts when validated with thousands or hundreds of thousands of images.…”
mentioning
confidence: 99%